Chinese Currency Devaluation and the Economic Implications for Nigeria - Okoyeuzu, Chinwe R.; Igwe, Anthony; Ukpere, Wilfred I. (Journal of Reviews on Global Economics, 2018)
The decision of Chinese government to devalue the Yuan has attracted serious condemnation by majorly developed economies, despite the government position that the devaluation was aimed at aligning the Yuan with the market rate. The general argument is anchored on the notion that the devaluation was a strategy to increase China's share of global trade by making its goods cheaper in the international market. This thinking is influenced by the long standing Mundell–Fleming model, which aligned with the theory that competitive devaluation is detrimental to the world economy, because of beggar-thy-neighbour welfare effect. The situation is compelling other countries to respond by improving their balance of trade in response to China tactics. The inability of developing economies to respond to this global trade war could be attributed to factors such as colonialism, presence of agency of restraints, complementarity among developing countries, and other institutional rigidities such as technological deficiency, infrastructure deficit, and commodity based exports, among others. Chinese currency devaluation has impacted meaningfully on the Nigeria economy given the fact that Nigeria maintains strong economic ties with China. The paper argues that for developing economies to effectively respond to competitive devaluation, they must close their borders to certain goods, improve infrastructure, prioritize technological transfer, embrace value-added production, and eliminate institution rigidities that hinder the ease of doing business.